Viabilidade do uso de extrato total aquoso de café verde (coffea canephora) como antioxidante em maionese em substituição a agentes sintéticos - Polvarini, Gisele da Silva (2023)
Mayonnaise, one of the most globally consumed sauces, is known for its high lipid concentration, making it susceptible to oxidation. To meet the current trend of products with clean label, there is a demand for plant antioxidants. Furthermore, the state of Espírito Santo (ES) is a significant coffee producer, in which the mature unroasted grain coffee beans are rich in antioxidant compounds, such as chlorogenic acid and caffeine. This study aimed to evaluate the feasibility of using aqueous green coffee extract as an antioxidant in mayonnaise, replacing the synthetic antioxidants usually used. Conilon coffee beans obtained from producers in the Caparaó region (ES) were crushed and the extract was obtained by percolation. The extract was analyzed for total phenolic content (TPC), antioxidant activity, and levels of caffeine and chlorogenic acid (5-O-ACQ). After chemical characterization, the extract was incorporated into mayonnaise formulations in proportions of 0.5%, 1%, and 1.5% (w/w). Formulations with BHT, BHA, and citric acid were prepared as positive controls (CTP). The samples were stored by 28 days to physical and chemical analysis. The texture profile of F1.5 differed from CTP after 28 days of storage, only in terms of hardness, and there was no difference in relation to the other parameters. F1.5 ensured stability in relation to total antioxidant activity, TPC, and 5-O-ACQ and caffeine content throughout the experiment. The incorporation of the extract increased the TPC of mayonnaises by up to 77%, enhancing its antioxidant activity. Mayonnaise with the extract showed a progressive lower increase in peroxide when compared to CTP, up to 21 days. The peroxide index at day 28 was the same for the CTP and F1.5 formulations. The incorporation of green coffee extract did not affect the sensory acceptance of mayonnaise. In conclusion, the application of aqueous Conilon green coffee extract as an antioxidant in mayonnaise, as a substitute for synthetic antioxidants, proved to be viable, especially at a concentration of 1.5%.